Current topics in developmental biology. Volume 34 - Schatten, Gerald; ScienceDirect eBooks (New York : Academic Press, 1996)
Volume 34 continues the series' tradition of timely review and incisive analyses of key research in developmental biology. Not only valuable to researchers at the forefront of animal and plant development, this volume is also a friendly introduction to students and professionals who are curious about current topics in cellular and molecular mechanisms in development.
SRY and mammalian sex determination / Andy Greenfield and Peter Koopman -- Transforming sperm nuclei into male pronuclei in vivo and invitro / D. Poccia and P. Collas -- Paternal investment and intracellular sperm-egg interactions during and following fertilization in drosophila / Timothy L. Karr -- Ion channels : key elements in gamete signaling / Albert Darszon, Arturo Lievano, and Carmen Beltran -- Molecular embryology of skeletal myogenesis / Judith M. Venuti and Peter Cserjesi -- Developmental programs in bacteria / Richard C. Roberts, Christina D. Mohr, and Lucy Shapiro -- Gametes and fertilization in flowering plants / Darlene Southworth.
Includes index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Embryology; Cytogenetics; SCIENCE -- Life Sciences -- Developmental Biology; Cytogenetics; Embryology; Electronic books